(untitled) (Global Journal of Human-Social Science, 2020)
This research aims to identify how marginal sexual practices influence the legal social sciences. From the analysis of the famous Brazilian case involving the travesty Indianara Siqueira as well as the study of the cases of first impressions R v. Brown and Pay v. UK, both ruled in the United Kingdom, it appears that both the traditions of common and civil law are insufficient to understand conflicts related to sexuality because they are based on the dogma of legal completeness. Finally, the development of a democratic right to sexuality is presented as a thesis for resolving the conflict, guided by the principles of freedom, equality, and dignity of the person. The hypothetical-deductive method was adopted based on a literature review.